Factors Affecting the Failure of Thai Education to Equip Thai Students with 21st Century Skills - Sanguanngarm, Nittaya (Community and Social Development Journal, 2020)
This study investigated the factors affecting the failure of Thai education to equip Thai students with 21st century skills. Participants in the study were forty teachers and ten principals in primary and secondary schools with ICT infrastructure and computing facilities in Chiang Mai, Thailand. The data were obtained using both stratified random sampling as well as purposive sampling methods. Data were complied through interviews, questionnaires, and teaching observations during 2018 academic year. The quantitative data were analyzed by means of descriptive statistics while the qualitative data were analyzed by content analysis using Hyper Research Program. The findings illustrate that desired learners’ key competencies indicated in the basic Thai education core curriculum were effective and met 21st century education. However, those factors that could affect the failure of Thai education to equip Thai students with 21st century skills include: 1) no inclusive evidence that there is a close link between desired learners’ key competencies and policy implementers’ practices including school administrators and teachers, 2) teachers’ and principals’ lack of understanding regarding the curriculum’s expectations and goals, as well as innovative teaching approaches and 21st century education in general 3) teachers’ and principals’ perception of students being dependent learners, and the idea that innovative teaching methods did not suit the contexts. Interestingly, the findings reveal that the teachers’ cultures and beliefs had a correlation influencing their teaching practices.